ANALISA MANAJEMEN RISIKO APLIKASI E-OFFICE MENGGUNAKAN ISO 31000:2018 PADA LEMBAGA KEBIJAKAN PENGADAAN BARANG/JASA PEMERINTAH (LKPP) - Arif, Gunawan Syarifah; Erliani, Yustika; Ratnasari, Anita (Universitas Airlangga, 2024)
The National Public Procurement Agency (NPPA/LKPP) has implemented the E-Office application to streamline work activities for both civil servant (ASN) and non-ASN employees, encompassing personnel data, attendance, correspondence, and other administrative functions. This research aims to identify and analyze the risks associated with the LKPP E-Office application. This study utilized a qualitative methodology, adhering to the ISO 31000:2018 risk management framework, to conduct in-depth interviews and observations within the LKPP setting. The aim was to gather comprehensive data to support stakeholders in making well-informed and precise policy decisions about the E-Office application. Through this research, 32 distinct risks were identified and categorized into high, moderate, and low levels based on their potential impact. This study developed specific mitigation strategies to address and minimize the effect of identified risks. By adopting these strategies, the research aims to enhance the reliability and security of the E-Office application. Improved risk management practices will lead to a more resilient and secure system. As a result, boosting administrative efficiency and data management capabilities within NPPA/LKPP. Furthermore, this research not only brings to light the critical areas that require immediate attention but also outlines a strategic roadmap for mitigating these risks. This approach ensures the sustainable and efficient operation of the E-Office application. The outcomes of this study are anticipated to offer substantial benefits to stakeholders, creating a more secure and efficient administrative environment.